PENERAPAN ISO 29119 SEBAGAI UPAYA PENINGKATAN KUALITAS LAYANAN WEBSITE E-PROCUREMENT - Salsabila, Diana Sava; Ardilla, Yunita; Wahyudi, Noor (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
Advances in information technology have encouraged companies to use digital platforms such as e-procurement, which can improve efficiency, transparency, and accountability in the procurement process. However, without thorough testing, these systems are at risk of functional errors and a decline in user trust. Previous research using black box testing methods and automation tools such as Katalon Studio can improve error detection, but there are still weaknesses in terms of validation and documentation consistency, meaning that the reliability of the system is not yet fully guaranteed. This study applies the ISO 29119 international standard as a structured framework, combined with black box testing methods and the Katalon Studio automated testing tool in testing the e-procurement website of PT. XYZ. Testing focused on four main features including registration, login, profile editing, and password change, with a total of 44 test cases. The evaluation results showed that 41 test cases were successful and 3 failed, mainly in the aspects of input validation and mandatory field labeling. The recommendations proposed include strengthening input validation, providing mandatory labels, and more informative error messages. This study shows that the implementation of ISO 29119 improves transparency, professionalism, and system reliability, making e-procurement services more secure and user-friendly.